2009
DOI: 10.1530/eje-08-0519
|View full text |Cite
|
Sign up to set email alerts
|

Increased reverse triiodothyronine is associated with shorter survival in independently-living elderly: the Alsanut study

Abstract: Objective: Increased reverse tritiodothyronine (T 3 ) used to be described as a part of euthyroid sick syndrome (ESS). It was demonstrated to be associated with increased mortality in acutely ill patients. It can also be found with low or normal T 3 in non-severely ill subjects but its significance remains unclear. Patients and design: The Alsanut study included a representative sample of 440 independently-living subjects aged 65 or over constituted between January 1988 and September 1989. Past and current med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Other hormonal changes including thyroid-stimulating hormone (TSH), free thyroxine (FT4) and triiodothyronine (FT3) have also been evaluated on their link to health outcomes in elderly, but only low FT3 levels were associated with an increased risk for morbidity and mortality [ 22 ]. These findings are consistent with other studies investigating aged populations, showing an association of low serum FT3 with reduced parameters of physical performance and muscle strength [ 51 ], as well as an increased disease-burden and mortality [ 51 , 52 ].…”
Section: Blood-based Candidate Biomarkerssupporting
confidence: 92%
“…Other hormonal changes including thyroid-stimulating hormone (TSH), free thyroxine (FT4) and triiodothyronine (FT3) have also been evaluated on their link to health outcomes in elderly, but only low FT3 levels were associated with an increased risk for morbidity and mortality [ 22 ]. These findings are consistent with other studies investigating aged populations, showing an association of low serum FT3 with reduced parameters of physical performance and muscle strength [ 51 ], as well as an increased disease-burden and mortality [ 51 , 52 ].…”
Section: Blood-based Candidate Biomarkerssupporting
confidence: 92%
“…does not intensify the activity of the pathway for the production of rT3. The decrease in rT3 concentration is also explained by its redistribution from vessels to extravascular space and the increase of rT3 cellular uptake [23]. In the present study, lower rT3 values were observed in dialysis patients than in patients without RF.…”
Section: Original Papersupporting
confidence: 56%
“…IV). Positive correlation between concentrations of rT3 and total protein was found in patients without ESRD, but this might be associated with the nutrition status of the patients [6,23]. Treatment with thyroid hormones in this group of patients did not change the conversion rates (Tab.…”
Section: Original Papermentioning
confidence: 87%
“…Except for the well-described prognostic significance of NTIS in the severity of illness and mortality of hospitalized patients, the Alsanut study of Forestier et al [14] evaluated a non-severely ill elderly population and revealed a negative correlation between rT3 levels and time to death, suggesting that elevated rT3 levels might reflect declining health.…”
Section: Definition and Thyroid Profile Of Ntismentioning
confidence: 99%